Ablation of the Locus Coeruleus Increases Oxidative Stress in Tg-2576 Transgenic but Not Wild-Type Mice - Hurko, Orest; Boudonck, Kurt; Gonzales, Cathleen; Hughes, Zoe A.; Jacobsen, J. Steve; Reinhart, Peter H.; Crowther, Daniel (International Journal of Alzheimer’s Disease, 2010)
Mice transgenic for production of excessive or mutant forms of beta-amyloid differ from patients with Alzheimer's disease in the degree of inflammation, oxidative damage, and alteration of intermediary metabolism, as well as the paucity or absence of neuronal atrophy and cognitive impairment. Previous observers have suggested that differences in inflammatory response reflect a discrepancy in the state of the locus coeruleus (LC), loss of which is an early change in Alzheimer's disease but which is preserved in the transgenic mice. In this paper, we extend these observations by examining the effects of the LC on markers of oxidative stress and intermediary metabolism. We compare four groups: wild-type or Tg2576 Aβ transgenic mice injected with DSP4 or vehicle. Of greatest interest were metabolites different between ablated and intact transgenics, but not between ablated and intact wild-type animals. The Tg2576_DSP4 mice were distinguished from the other three groups by oxidative stress and altered energy metabolism. These observations provide further support for the hypothesis that Tg2576 Aβ transgenic mice with this ablation may be a more congruent model of Alzheimer's disease than are transgenics with an intact LC.